Combination on endophytic fungal as the Plant Growth-Promoting Fungi (PGPF) on cucumber (Cucumis sativus) - Syamsia Syamsia; ABUBAKAR IDHAN; AMANDA PATAPPARI FIRMANSYAH; NOERFITRYANI NOERFITRYANI; IRADHATULLAH RAHIM; HENRY KESAULYA; RAKHMAD ARMUS (Society for Indonesian Biodiversity, 2021)
Abstract. Syamsia S, Idhan A, Firmansyah AP, Noerfitryani N, Rahim I, Kesaulya H, Armus R. 2021. Combination on endophytic fungal as the Plant Growth-Promoting Fungi (PGPF) on Cucumber (Cucumis sativus). Biodiversitas 22: 1194-1202. Endophytic fungi are known to stimulate plant growth by producing secondary metabolites, including phytohormones (IAA and Gibberellins), siderophore, phosphate-solubilizing metabolites. In this study, a total of six endophytic fungi were successfully isolated from local rice plants and showed different abilities in producing secondary metabolites, during single isolates testing. These six isolates were then combined to obtain 15 combinations for analysis, to determine the best combination for application as a plant growth promoter. Subsequently, each combination was tested for phytohormones (IAA, gibberellins) and siderophore (quantitatively)-producing activity, phosphate-solubilizing ability, and the effect on cucumber (Cucumis sativus L) plant growth. F13 showed activity in producing IAA and produced the highest gibberellin levels, while F1 exhibited the highest phosphate-solubilizing activity. In addition, F11 (Na-salicylate) and F1 (catechol) showed the highest siderophore activity, while a combination of F6, F8, F9, and F12 successfully increased plant height growth. Also, F4 increased the root growth, while the fresh weight of cucumber was increased by F8 treatment, under controlled conditions. Molecular analysis showed the tested isolates have close similarity to Daldinia eschscholtzii, Sarocladium oryzae, Rhizoctonia oryzae, Penicillium allahabadense, and Aspergillus foetidus. The combination of endophyte fungal isolates showed potential as plant growth promoters, however, further testing on several plant types is required before the combination is to be widely applied.